2020
DOI: 10.1007/s42399-020-00593-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in HIV: a Review of Published Case Reports

Abstract: Patients with COVID-19 present with a myriad of comorbidities. An immunocompromised state like HIV in patients with COVID-19 can be life-threatening. We searched PubMed/Medline, Scopus, and Web of Science for case reports and case series about COVID-19 in HIV patients. We finally reviewed 20 case reports including cases of 43 patients with HIV and COVID-19. The mean age of 43 adult patients was 51.56 ± 27.56 years (range 24–76 years). Of these, 30 were male (69.77%), 11 were female (25.58%), and 2 were transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…19 20 Men who have sex with men, and transgender women, have higher rates of HIV, which may exacerbate the effects of the COVID-19 virus. 21 In addition, it has been demonstrated that the greater the level of minority stress on a person from the sexual minority community, the greater the negative impact on their mental health. 22 Minority stress may also adversely affect their physical health.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…19 20 Men who have sex with men, and transgender women, have higher rates of HIV, which may exacerbate the effects of the COVID-19 virus. 21 In addition, it has been demonstrated that the greater the level of minority stress on a person from the sexual minority community, the greater the negative impact on their mental health. 22 Minority stress may also adversely affect their physical health.…”
Section: Open Accessmentioning
confidence: 99%
“… 19 20 Men who have sex with men, and transgender women, have higher rates of HIV, which may exacerbate the effects of the COVID-19 virus. 21 …”
Section: Introductionmentioning
confidence: 99%
“…1 During lockdown, some of the international scientific societies suggested to postpone HIV care visits for steady patients and screening for most sexually transmitted infections (STIs), to reduce SARS-CoV-2 spreading. 2 Currently, our knowledge concerning whether or not people living with HIV (PLWH) are at a higher risk of severe COVID-19, 3,4 or whether antiretroviral medications used to treat HIV may be protective against severe COVID-19 5 is still limited. As a matter of fact, most of the PLWH hospitalized because of SARS-CoV-2 infection were also affected by other comorbidities, including cardiovascular diseases and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Immunocompromised populations (for example, people receiving cancer therapies such as chemotherapy, radiotherapy, and immunotherapy; and individuals with HIV) appear more likely to contract COVID-19. 8 , 9 Comorbidities such as hypertension, diabetes mellitus, cardiovascular diseases, and chronic obstructive pulmonary diseases are also common among those with COVID-19. 10 To compound matters, individuals with pre-existing health conditions are often more susceptible to severe COVID-19-related illness and injury.…”
Section: Introductionmentioning
confidence: 99%
“… 10 To compound matters, individuals with pre-existing health conditions are often more susceptible to severe COVID-19-related illness and injury. At-risk populations include those with weaker immune systems (for example, recipients of immunosuppressant therapy and populations with HIV), 8 , 9 and those with chronic health conditions such as hypertension, 10 , 11 diabetes, 10 , 11 cardiac illnesses, 4 , 10 12 chronic lung disease, 13 liver disease, 14 haematological malignancy, 15 chronic kidney disease, 16 and neurological conditions including dementia, Parkinson’s, epilepsy, multiple sclerosis, and spinal cord injury. 16 Evidence regarding COVID-19-related health impacts for groups — including pregnant patients and their babies, 17 patients who are immunocompromised, patients with diabetes, 9 , 18 and patients with asthma 19 — is mixed in terms of clinical outcomes and evidence availability.…”
Section: Introductionmentioning
confidence: 99%